Nuclear magnetic moment of the $^{57}$Cu ground state (I=3/2$^-$, T$_{1/2}$=199.4 ms) - Minamisono, K.; Mantica, P.F.; Mertzimekis, T. J.; Davies, A.D.; Hass, M.; Pereira, J.; Pinter, J.S.; Rogers, W. F.; Stoker, J.B.; Tomlin, B.E.; Weerasiri, R.R. (Phys. Rev. Lett., 2006)
The nuclear magnetic moment of the ground state of Cu57(I?=3/2-,T1/2= 196.3ms) has been measured to be |?(Cu57)|=(2.00±0.05)?N using the ?-NMR technique. Together with the known magnetic moment of the mirror partner Ni57, the spin expectation value was extracted as ??z =-0.78±0.13. This is the heaviest isospin T=1/2 mirror pair above the Ca40 region for which both ground state magnetic moments have been determined. The discrepancy between the present results and shell-model calculations in the full fp shell giving ?(Cu57)?2.4?N and ??z ?0.5 implies significant shell breaking at Ni56 with the neutron number N=28. © 2006 The American Physical Society.